High expression of CX3C chemokine receptor 1 (CX3CR1) in human carotid plaques is associated with vulnerability of the lesions - Masztalewicz, Marta; Nowacki, Przemysław; Szydłowski, Łukasz; Żukowski, Maciej; Gutowski, Piotr (Folia Neuropathologica, 2017)
Introduction : In data based on ex vivo studies and animal models, fractalkine is considered an important mediator in the development and destabilization of atherosclerotic plaques. We do not know how it is associated with human carotid plaques morphology. Material and methods : The study included 126 carotid plaques taken from 126 patients who underwent endarterectomy of internal carotid arteries. We assessed the following characteristics: inflammatory infiltration, connective tissue elements, foam cells, lipid core, plaque vascularisation, calcifications, intraplaque haemorrhage, thrombi built into the plaque structure, and mural thrombi. CX3CR1 expression in plaques as a response to fractalkine was assessed. Results : Compared to those with a low fractalkine receptor expression, plaques with its high expression exhibited more intensive inflammatory infiltrations. They were more likely to contain inflammatory than fibrous components. They were characterized by a large foam cell component and were less calcified. Intraplaque haemorrhages, the large lipid core and mural as well as intraplaque thrombi were more frequent within them. Conclusions : High expression of the fractalkine receptor within human carotid plaques is associated with morphological parameters of plaque instability. Thus we conclude that fractalkine may be involved in vulnerability of human carotid plaque.